Association of Serum Immunoglobulins Levels With Specific Disease Phenotypes of Crohn's Disease: A Multicenter Analysis in China - Song, Dong Juan; Shen, Jun; Chen, Min Hu; Liu, Zhan Ju; Cao, Qian; Hu, Pin Jin; Gao, Xiang; Qian, Jia Ming; Wu, Kai Chun; Lai, Li Jie; Ran, Zhi Hua (Frontiers in Medicine, 2021)
Background and Aim: Serum immunoglobulins were reported to be associated with clinical characteristics of inflammatory bowel disease. However, whether a difference exists in the serum immunoglobulins levels in patients with Crohn's disease (CD) with different disease location and behavior phenotypes remains unclear. Therefore, this study aimed to explore the associations of serum immunoglobulins levels with specific CD phenotypes. Methods: Patients with CD having recorded serum immunoglobulins levels were recruited through multicenter collaborative efforts. The associations between serum immunoglobulins levels and distinct phenotypes of CD were evaluated using multiple logistic regression models. Results: A total of 608 patients with CD were included in the study. Elevated (above the upper limit of normal) serum immunoglobulin G (IgG), IgA, IgM, and IgG4 were identified in 24.5, 17.4, 2.1, and 8.2% of patients, respectively. Elevated serum IgG4 levels negatively correlated with complicated disease behavior [odds ratio (OR) 0.49, 95% confidence interval (CI) 0.26–0.92]. Elevated serum IgG was linked to isolated ileal disease with an OR of 0.37 (95% CI 0.23–0.61). The ORs of isolated ileal disease progressively reduced across increasing quartiles of IgG (P for trend < 0.001). The adjusted ORs of isolated ileal disease for increasing quartiles of IgM were 1.82 (1.07–3.1), 1.92 (1.14–3.24), 1.17 (0.69–1.98), and 1 (P for trend = 0.008). Besides, serum IgA and IgG levels significantly correlated with several disease activity indices. Conclusions: These results suggested that certain serum immunoglobulins were associated with specific disease phenotypes of CD. Further investigations to account for the associations are warranted.